Triassic extensional tectonics at the northern branch of the Cuyana basin (South Precordillera): First kinematic data - Japas, M.S. (2008)
Triassic clastic and volcanic rocks from the Precordillera were deposited in the Cuyana rift basin filling half-graben systems. Contractional/transpressional Andean tectonics leads to the almost complete inversion of some portions of the basin which resulted in present-day isolated, structurally controlled outcrops of these Triassic rocks. In the Southern Precordillera both the degree of Neogene tectonic inversion and structural compexities are variable. At the regional scale, these variations in Andean deformation are related to first order anisotropies like the Cuyana basin borders and previous shear zones of Permian age (San Rafael orogenic phase). This paper focuses on the kinematic analysis done in the Cerro Manantial thrust sheet area (Cordón San Bartolo, central sector of the South Precordillera) where tectonic inversion was not that strong and the influence of oblique strain zones is practically null. Four sets of extensional/ transtensional faults were recognized affecting Triassic sedimentary rocks of the El Cielo Formation (Uspallata Group) at the Quebrada El Salto. Fault displacements are of decimetric to metric scale. Mesoscopic kinematic indicators (en-échèlon tensional gashes, Riedel shear fractures, sigmoidal fractures) were measured. Once Andean deformation was restored, a NNE direction for the Triassic extension was determined. Considering a northern branch of the Cuyana basin trending NNW (Az. 150°) and oblique to the direction of extension (Az. 35-40°), a sinistral strike-slip component could be inferred for this portion of the basin.